Effects of Obesity on Pro-Oxidative Conditions and DNA Damage in Liver of DMBA-Induced Mammary Carcinogenesis Models - Melnyk, Stepan (Metabolites, 2017)
The prevalence of the overweight and obesity is on the rise worldwide. Obesity can increase the risk of certain cancers and liver steatosis development. Previously, we reported that obesity increased liver steatosis in a mammary tumor model, but little is known about the effects of obesity in the liver in regard to global DNA methylation, DNA damage, and oxidative/nitrosative stress. Using a mammary tumor model, we investigated the effects of obesity on oxidative stress and DNA reaction. Five-week-old lean and obese female rats were used. At 50 days of age, all rats received 7,12-dimethylbenz(α)anthracene (DMBA) and were sacrificed 155 days later. HPLC with electrochemical and ultraviolet detection and LC-MS were used. Obesity caused higher (p < 0.0004) methionine levels, had no effect (p < 0.055) on SAM levels, caused lower (p < 0.0005) SAH levels, caused higher (p < 0.0005) SAM/SAH ratios, and increased (p < 0.02) global DNA methylation. Levels of free reduced GSH were not significantly lower (p < 0.08), but free oxidized GSSG was higher (p < 0.002) in obese rats. The GSH/GSSG ratio was lower (p < 0.0001), and oxidized guanosine was higher (p < 0.002) in DNA of obese rats compared to lean rats. Obesity caused significant oxidative/nitrosative stress, oxidative DNA damage, and change of DNA methylation pattern in the liver, and these changes may contribute to the development of liver steatosis in breast cancer models.